A Monitoring Kualitas Kaca Panasab dengan Diagram Kontrol MEWMA - wibawati, Wibawati; Fadhila, Amalia Nur (Proximal: Jurnal Penelitian Matematika dan Pendidikan Matematika, 2023)
Panasab glass is one type of glass that can absorb some of the heart's heat so that the temperature in the room is more comfortable. One of the national glass companies that produce hot glass monitors the silvering coating process. The silvering method is considered less effective because it is expensive. Therefore, in this paper, the process of controlling the quality of hot glass is carried out on the quality characteristics of the left and right CD edge distortion, which is the length of the roll marks on the right and left sides of the net glass that affect the presence or absence of distortion in the visual check results. The two quality characteristics correlate with each other. Therefore, quality control is carried out using a Multivariate Exponentially Weighted Moving Average (MEWMA) control chart to monitor process variability and averages. MEWMA control chart statistics are affected by the weighting value . The quality characteristic data of panasab glass is divided into phase 1 and phase 2. Phase 1 is used to obtain an in-control parameter estimate (IC) which is then used for monitoring phase 2. Quality monitoring in phase 1, the process has been statistically controlled after iterations have been carried out. By using =0.4. Meanwhile, phase 2, based on the MEWMA control chart, shows that the producton procrss of panasab glass production has not been controlled statistically. Based on process capability analysis, the results obtained that the level of precision and accuracy of the quality of panasab glass products is still low. So it can be concluded that the production process of panasav glass is not yet capable.